Fronto‐Insular Connectivity during Pain Distraction Is Impaired in Patients with Somatoform Pain. Issue 6 (20th July 2018) - Stankewitz, Anne; Sorg, Christian; von Kalckreuth, Alexander; Schulz, Enrico; Valet, Michael; Neufang, Susanne; Zimmer, Claus; Henningsen, Peter; Gündel, Harald; Wohlschläger, Afra M.; Tölle, Thomas R.
ABSTRACT: BACKGROUND AND PURPOSE: Somatoform pain disorder is characterized by chronic pain and various psychological symptoms including increased attention to mental and physical processes. Given that the medial prefrontal cortex (mPFC) of the default mode network (DMN) and the anterior insula of the salience network are critically involved in intrinsic and attentional processes, we investigated the involvement of these networks during the distraction from physical pain in somatoform pain patients. METHODS: During painful and nonpainful heat stimulation, attentional distraction from physical processes was modulated with a Stroop task. Thirteen patients were investigated with functional magnetic resonance imaging (fMRI) and compared to 13 controls. Main outcomes were spatial maps of coherent fMRI activity based on independent component analysis and functional connectivity (FC) resulting from psychophysiological interaction analysis. RESULTS: Behavioral pain intensity ratings were reduced during the distraction task in both groups. At brain level, we found deviant network activities in the DMN (particularly in the mPFC) and in the salience network (bilaterally in the anterior insula) in patients. During pain stimulation, Stroop‐induced distraction decreased the FC between the mPFC and anterior insula in controls but not in patients. CONCLUSIONS: Modulating the FC between the mPFC and the insula may be highly relevant for shifting the attention away from external stimuli, including nociceptive input. The observed alterations in somatoform pain patients may foster new strategies in cognitive behavioral training tools for these patients.